2007
DOI: 10.1111/j.1600-0536.2007.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact sensitivity and atopic dermatitis: association with prognosis, a follow‐up study in 801 atopic patients

Abstract: The influence of contact sensitivities on the course of atopic dermatitis (AD) is not known. The objective of the study is to find the course of AD in atopic patients with and without contact sensitivities. A total of 801 atopic patients were studied and patch tested in 1983/84. A questionnaire focusing on the occurrence of dermatitis was sent to these patients 16 years later. During the follow up the number of symptom-free patients increased from 36.7% to 40.7%. In patients with positive patch-test reactions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
(34 reference statements)
2
4
0
Order By: Relevance
“…The elimination of responsible allergens could improve the SCORAD score and prolong the remission periods in individuals with AD 25 . We similarly noted improvement of lesions in most of the followed-up children when elimination was possible.…”
Section: Discussionsupporting
confidence: 63%
“…The elimination of responsible allergens could improve the SCORAD score and prolong the remission periods in individuals with AD 25 . We similarly noted improvement of lesions in most of the followed-up children when elimination was possible.…”
Section: Discussionsupporting
confidence: 63%
“…The finding of a higher rate of sensitization to potassium dichromate in the AI group was unexpected, although other studies have also reported this allergen as a frequent sensitizer among AIs, with sensitization rates as high as 7.9% 6,12,14,15 . Another investigation showed that this antigen sensitized 2.6% of subjects among a pediatric population of 137 atopic children 10 .…”
Section: Discussionmentioning
confidence: 82%
“…The finding of a higher rate of sensitization to potassium dichromate in the AI group was unexpected, although other studies have also reported this allergen as a frequent sensitizer among AIs, with sensitization rates as high as 7.9%. 6,12,14,15 Another investigation showed that this antigen sensitized 2.6% of subjects among a pediatric population of 137 atopic children. 10 Because exposure to dichromates, such as are found in cement and leather, is uncommon in childhood, it is conceivable that this study's results 10 may have included subjects with irritant contact dermatitis, rather than a true contact allergy.…”
Section: Discussionmentioning
confidence: 99%
“…One study even showed that after a diagnosis of contact allergy was demonstrated, a reduction of dermatitis in adults was seen, possibly because the allergen could be avoided (7).…”
mentioning
confidence: 97%